HUBUNGAN TITER WIDAL DENGAN JUMLAH LIMFOSIT PADA KASUS DEMAM TIFOID DI WILAYAH KERJA PUSKESMAS SAWOO - Yaninda Setyanti Ekasari; Dewi Saroh (Jurnal Analis Laboratorium Medik, 2021)
Typhoid fever is a systemic infection that is still a global problem, especially in Indonesia. This disease is caused by Salmonella bacteria. The Widal test is used to detect antibodies to Salmonella bacteria based on agglutination reactions between bacterial antigens and antibodies called agglutinins. Routine blood tests be used to see the body's defense mechanism against infection. Lymphocytes are produced by bone marrow, the presence of bacterial endotoxin causes inhibition of the formation of lymphocytes, so that in some cases of typhoid fever, low lymphocyte counts are often found. The purpose of this study was to determine the relationship between Widal titer and lymphocyte count in patients with suspected typhoid fever. The Widal test was examined using a microscope to see the agglutination formed, while the number of lymphocytes was calculated using a hematology analyzer. The results of the Widal test with a titer of 1/160 were 63.3% with normal lymphocyte counts and 10% with low lymphocytes. While the titer 1/320 obtained 10% of respondents with normal lymphocyte count and 16.7% with low lymphocyte count. The research design used was analytic observation with the type of cross sectional study. Statistical analysis using Kendall's Tau-b correlation test with SPSS. From the correlation test, the significance value is 0.009, and the correlation coefficient is -0.404**, which means that there is a relationship between the Widal titer and the number of lymphocytes with sufficient closeness.